Мотель смертников: роман / Н. Леонов, А. Макеев - Леонов Николай (Русский бестселлер, 2011)
Экземпляры: Ф. 13 (20200131) / Инвентарный номер: 47563 / Цена: 20.00 / Сис.шифр: 84(2=411.2)6-44 / Авт.знак: Л 47 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-44